A prototype application for helping to teach how to read numbers - Vítor Manuel Ferreira Alves Carvalho (2003)
Nowadays we see several multimedia math applications in support of teaching the basic operations, geometric analysis, algebra and other complex operations; however there's no math application for the children at starting school age that helps to teach how to read a number in Portuguese. The Laboratory for Speech Processing, Electro Acoustics, Signals and Instrumentation (LPF-ESI) at the Faculty of Engineering of the University of Porto (FEUP), started a project using a text-to-speech (TTS) engine and a Visual Basic multimedia application in order to fulfil that gap. A prototype has been produced, called "A Quinta dos Números" (AQN) (The Farm of Numbers), that intends to create a bridge between engineering, computer science and pedagogy, using psycho-pedagogic concepts inherent to the teaching of maths, artificial intelligence, speech/text processing and multimedia systems, as scientific basis. Develop to help the teacher to consolidate the student's knowledge and to support a progressive evaluation of her/his performance, AQN offers a multimedia interaction with speech synthesis and text boxes. It allows a greater accessibility at the same time it will offer a wide choice of didactic games, with learning and evaluation aims.